COMMUNICATIVE APPROACH TO TEACHING ENGLISH AT TECHNICAL UNIVERSITIES - M. V. Shevchenko (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2015)
The article deals with the communicative approach to teaching English at technical universities. The constituents of the communicative competence are presented. Differentiation between two ways (strong and weak versions) of development of students' communicative abilities can also be found in the proposed paper. The distinction lies in variance of ways of the English language acquisition by students, including those of technical specialities. The work contains lists of peculiarities of explicit/implicit learning and teaching with the help of communicative language teaching (CLT). Their positive sides and weaknesses are considered. Three central areas of explicit-implicit teaching - focus on form and form-focused instruction, fluency and automation, formulaic language - are also reviewed. The main attention of the article is paid to the aim, key characteristics and principles of the approach in question, as well as to advantages and disadvantages of the communicative approach use at the English language lessons. Among quality assessment criteria of the communicative teaching are efficiency of the English language acquisition, novelty of materials, and also effectiveness of educators' and students' work. Recommendations for teachers, concerning the proper CLT implementation at the lessons of English for Specific Purposes, and features of recommended classroom activities to do so are provided at the end of the article.